PROBLEMATIKA KESETARAAN GENDER DAN PERLINDUNGAN HAM DALAM PENERAPAN HUKUM - Marlini Marlini; Jusmiwarti BJ (STKIP Pesisir Selatan, 2026)
Gender equality and the protection of human rights are crucial issues in the social, political and legal context in Indonesia. This article aims to analyze the understanding and application of gender equality in a legal perspective, evaluate the challenges of human rights protection, and identify the problematic application of law in various sectors. This research uses a qualitative approach with a literature study method through documentation techniques and descriptive analysis. The results of the study show that although Indonesia has ratified international instruments such as CEDAW and has regulations that protect gender equality, its implementation still faces significant obstacles in the form of a wage gap, limited access to education for women in rural areas, injustice in inheritance law, and weak law enforcement against gender-based violence. Patriarchal cultural factors, gender bias of law enforcement officials, and lack of public legal awareness are the main obstacles. The implications of this research emphasize the need for gender-responsive legal reform, increasing the capacity of law enforcement officials, and strengthening public education and legal awareness as the basis for formulating inclusive and equitable legal policies to strengthen human rights protection in Indonesia.